“Why Them, Not Me?”: A Study Exploring The Impact Of Following Fashion Influencers on Instagram on Body Image Satisfaction of Adolescent Girls and Middle-aged Women - Panjrath, Yashvi; Tiwari, Savita (International Journal of Psychosocial Rehabilitation, 2024)
The ongoing interference of social media in our daily lives makes it necessary to explore its impact onmental health. Instagram provides a platform to follow fashion influencers to be updated about fashiontrends and tips. These influencers pose a perfect life on social media creating an unrealistic standard forideal body. Thus, the current study aimed to study whether following fashion influencers on Instagramlead to body image dissatisfaction among Adoloescentgirls and middleaged women. From the datacollected it was found that following fashion influencers has been found to have an impact on thefollowers in various ways, while it can be detrimental for the mental health and well-being of thefollowers leading to body image dissatisfaction, shrinking of self, it can also have a positive impact ontheir followers as it is found to develop motivation, inspiration among their followers and help makingthe followers aware and updated about latest trends